Integration Expectation Confirmation Theory and AISAS Model in Coffee Shop Repurchase Intention - Juliana Juliana; Marchell Felix Beanardo; Jessica Nethania Hering; Irene Jennifer; Ricky Ricky (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2021)
Kopi chuseyo is a coffee shop that stands in the middle of the proliferation of k-popers in indonesia. this coffee shop with a k-pop nuance gets loyal customers and has high purchasing power. kopi chuseyo elevates k-pop as an endorsement and brand image that differentiates it from other coffee shops by implementing a good marketing strategy to achieve a competitive advantage. the research objective was to develop a conceptual model of repurchase intention using the expectation confirmation theory AISAS (Attention, Interest, Search, Action, Share) Model. the population of this research is consumers who have ever consumed chuseyo coffee in indonesia. the sampling technique used non-probability sampling with a total of 108 respondents. the study results in a brand image significantly affected repurchase intention; celebrity endorsement advertisement had no significant effect on repurchase intention. Ckuseyo coffee must maintain the brand image that consumers feel to increase consumer repurchase intention.